Dock2 generates characteristic spatiotemporal patterns of Rac activity to regulate neutrophil polarisation, migration and phagocytosis - Machin, Polly A.; Johnsson, Anna-Karin E.; Massey, Ellie J.; Pantarelli, Chiara; Chetwynd, Stephen A.; Chu, Julia Y.; Okkenhaug, Hanneke; Segonds-Pichon, Anne; Walker, Simon; Malliri, Angeliki; Fukui, Yoshinori; Welch, Heidi C. E. (Frontiers in Immunology, 2023)
Rac-GTPases and their Rac-GEF activators play important roles in neutrophil-mediated host defence. These proteins control the adhesion molecules and cytoskeletal dynamics required for neutrophil recruitment to inflamed and infected organs, and the neutrophil effector responses that kill pathogens. Here, we used live cell TIRF-FRET imaging in neutrophils from Rac-FRET reporter mice with deficiencies in the Rac-GEFs Dock2, Tiam1 or Prex1/Vav1 to evaluate if these proteins activate spatiotemporally distinct pools of Rac, and to correlate patterns of Rac activity with the neutrophil responses they control. All the GEFs were required for neutrophil adhesion, and Prex1/Vav1 were important during spreading and for the velocity of migration during chemotaxis. However, Dock2 emerged as the prominent regulator of neutrophil responses, as this GEF was required for neutrophil polarisation and random migration, for migration velocity during chemokinesis, for the likelihood to migrate and for the speed of migration and of turning during chemotaxis, as well as for rapid particle engulfment during phagocytosis. We identified characteristic spatiotemporal patterns of Rac activity generated by Dock2 which correlate with the importance of the Rac-GEF in these neutrophil responses. We also demonstrate a requirement for Dock2 in neutrophil recruitment during aseptic peritonitis. Collectively, our data provide a first direct comparison of the pools of Rac activity generated by different types of Rac-GEFs, and identify Dock2 as a key regulator of polarisation, migration and phagocytosis in primary neutrophils.